Estudo da estabilidade de lipossomas compostos de fosfatidilcolina de soja e fosfatidilcolina de soja hidrogenada adicionados ou não de colesterol por método turbidimétrico - Chorilli, Marlus [UNESP]; Rimério, Thereana Cristina [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Scarpa, Maria Virgínia [UNESP] (My University, 2007)
Liposomes are structures composed by phospholipids as soy phosphatidylcholine (PC) and hydrogenated soy phosphatydylcholine (PCH). Among the methods used to prove liposomes stability, turbidity method is widely used. The objective of this work was to study the liposomes stability containing PC or PCH with and without cholesterol (CHOL) by turbidity method. Liposomes were stored a 30°C during 90 days and periodically absorbance readings at 410 nm were made to verify possible turbidity alterations. Increases in the turbidity with time occurred for PC liposomes. In the presence of CHOL higher turbidity was obtained probably reflecting the increase in the size of liposomes. For PCH liposomes the presence of CHOL did not affect the turbidity suggesting higher physical stability of the structures.
Study of liposomes stability containing soy phosphatidylcholine and hydrogenated soy phosphatydylcholine adding or not cholesterol by turbidity method
Keywords: Hydrogenated soy phosphatidylcholine; Liposomes; Soy phosphatidylcholine; Turbidity; cholesterol; liposome; phosphatidylcholine; hydrogenation; soybean; turbidimetry